The Effect of Taxpayer Knowladge and Perseption on Restautant Taxpaper Compliance In Makassar City Area Revenue Auhority - St. Fatimah B; Andi Aslinda; Andi Cudai Nur; Andi Muhammad Rivai (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine how much influence Taxpayer Knowledge and Awareness has on Restaurant Taxpayer Compliance at the Makassar City Revenue Agency. This study uses quantitative methods of descriptive research with data collection techniques through observation, questionnaires and documentation. The sampling method used is Nonprobability Sampling with Incidental Sampling Technique. The results of the study show that the knowledge of taxpayers has a positive effect on taxpayer compliance, taxpayer awareness has a positive effect on taxpayer compliance, and there is an effect of knowledge and awareness of taxpayers simultaneously or together on restaurant taxpayer compliance at the Makassar City Regional Revenue Agency.